2021
DOI: 10.1002/jpen.2263
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to nutrition therapy in the critically ill patient with COVID‐19

Abstract: Background Coronavirus disease 2019 (COVID‐19) has created challenges for intensivists, as high ventilatory demands and prolonged hypermetabolism make it difficult to sustain nutrition status. The purpose of this survey was to determine current practices in nutrition therapy and identify barriers to its delivery. Methods A survey about delivering nutrition therapy to critically ill patients with COVID‐19 was sent to clinicians at academic and community hospitals from Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
1
19
0
3
Order By: Relevance
“…Al Suliman et al (2022) demonstraram que determinadas barreiras são enfrentadas para o fornecimento de uma terapia nutricional adequada, o que prejudica o fornecimento de energia, de proteínas e demais nutrientes ao paciente. Dentre as barreiras mais citadas pelos profissionais envolvidos no estudo, o risco de aspiração da NE, os riscos de uma manutenção prolongada da NP e a evolução de forma abrupta dos pacientes foram as mais citadas.…”
Section: Terapia Nutricionalunclassified
“…Al Suliman et al (2022) demonstraram que determinadas barreiras são enfrentadas para o fornecimento de uma terapia nutricional adequada, o que prejudica o fornecimento de energia, de proteínas e demais nutrientes ao paciente. Dentre as barreiras mais citadas pelos profissionais envolvidos no estudo, o risco de aspiração da NE, os riscos de uma manutenção prolongada da NP e a evolução de forma abrupta dos pacientes foram as mais citadas.…”
Section: Terapia Nutricionalunclassified
“…Despite the significant complications associated with COVID-19, it would appear that only limited attention has been given to nutrition therapy as part of the broader supportive care for the patients [ 18 ]. However, enteral nutrition provision presents its challenges, including the potential for adverse reactions, such as abdominal distention, diarrhoea and regurgitation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified barriers in providing nutrition to this vulnerable group, including unpredictable clinical courses and fear of aspiration. 3 In this regard, we recognised that audit of local practices would make clinicians aware of the management gap, if any. There is currently only 1 local study (single-centre case series of 8 patients) that described the nutritional care of SARS-CoV-2 critically ill patients.…”
Section: Introductionmentioning
confidence: 99%